Forecasting stock quotations of PJSC NK Lukoil based on polynomial trend models - L.I. Tenkovskaya (Векторы благополучия: экономика и социум)
The article is devoted to the economic and mathematical modeling and forecasting stock quotations of PJSC NK Lukoil. Subject. Processes of forming the dynamics of the value of the studied company securities. Aim. To predict the stock prices of PJSC NK Lukoil by creating a new methodology for constructing second‐order polynomial trend models within the framework of economic cycles. Tasks. Include the consideration of the theoretical foundations, the creation and testing of a methodology for forecasting stock quotations of PJSC NK Lukoil. The author has put forward a scientific hypothesis, which consists in the fact that the share prices of PJSC NK Lukoil within the economic cycles form a dynamics corresponding to a parabola and described using the secondorder polynomial trend equation. Methods. Analysis, synthesis, monographic method, scientific abstraction, visual, centered moving average method, ADF test, KPSS test, economic and mathematical modeling, forecasting, graphical, tabular. The research methodology involves the creation of models of second‐order polynomial trends with the function of forecasting stock prices of companies within economic cycles beginning and ending with economic growth to calculate the maximum values of the cost of the investment assets of interest and the date of their achievement. Results. The second‐order polynomial model was built to predict the share prices of PJSC NK Lukoil, which signals the completion of the growth in the value of these securities within the current economic cycle. The scientific work done has theoretical and applied significance: it can serve as a basis for forecasting the value of shares of other companies; the forecast of stock quotations of PJSC NK Lukoil is a signal for investors to sell these securities. Areas of application of the results of scientific work: in trading on the Russian stock market; in corporate governance of public joint‐stock companies; in state regulation of the activities of domestic corporations that replenish the federal budget with revenues.